2017
DOI: 10.1007/s40037-017-0376-7
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines: The do’s, don’ts and don’t knows of direct observation of clinical skills in medical education

Abstract: IntroductionDirect observation of clinical skills is a key assessment strategy in competency-based medical education. The guidelines presented in this paper synthesize the literature on direct observation of clinical skills. The goal is to provide a practical list of Do’s, Don’ts and Don’t Knows about direct observation for supervisors who teach learners in the clinical setting and for educational leaders who are responsible for clinical training programs.MethodsWe built consensus through an iterative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
167
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(180 citation statements)
references
References 169 publications
(254 reference statements)
3
167
0
10
Order By: Relevance
“…The direct observation of trainees with patients allows highlevel impactful clinical feedback and provides a basis for calibrating how much autonomy to allow. 16 Trainees also indicate that teaching is more impactful during BSR than during walk rounding or card flipping, and clinical skill training during BSR is superior to a discussion in a conference room or a hallway context. 2,3,15,17,18 One study has even suggested that the education of bedside rounds may help improve clinical skills in comparison with traditional models.…”
Section: Why We Should Return To the Bedsidementioning
confidence: 99%
See 1 more Smart Citation
“…The direct observation of trainees with patients allows highlevel impactful clinical feedback and provides a basis for calibrating how much autonomy to allow. 16 Trainees also indicate that teaching is more impactful during BSR than during walk rounding or card flipping, and clinical skill training during BSR is superior to a discussion in a conference room or a hallway context. 2,3,15,17,18 One study has even suggested that the education of bedside rounds may help improve clinical skills in comparison with traditional models.…”
Section: Why We Should Return To the Bedsidementioning
confidence: 99%
“…9 This initiative starts by preparing ahead of time, which allows the mental energy during encounters to be directly observed by learners in action. 16 Preparation also allows the presentation to focus more on clinical reasoning rather than data gathering. 20 Faculty members should also consider ways to foster resident autonomy and establish the role of a supervising resident as the team leader.…”
Section: What We Should Do Insteadmentioning
confidence: 99%
“…Yet, as Kogan et al. also state, direct observation in medical education is often infrequent and of poor quality . We first discuss how recent research on optimising direct observation and feedback aligns with what we know about being a good clinical educator.…”
mentioning
confidence: 93%
“…We elaborate on this by zooming in on direct observation and feedback as central constituents of supervision. Direct observation is crucial for the purposes of feedback and assessment, as Kogan and colleagues describe in their guidelines on direct observation . Yet, as Kogan et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation